Retrofitting measures for reducing buildings cooling requirements in cooling-dominated environment: Residential house. (5th April 2016) - Kharseh, Mohamad; Al-Khawaja, Mohammed
Highlights: Performed calculations show that replacing single glazed window with double glazed reduces the cooling load by 4.5%. Adding 2 cm of Polyurethane to the external walls reduces the cooling load by 28%. 53% reduction in the cooling load can be obtained by implementing all measures. The payback period of considered retrofitting measures varies between 0.5 and 4 years. Abstract: Air conditioning systems in hot and developing countries are the major energy consumers. Unfortunately, Arabian Peninsula countries still rely completely on fossil fuel. Therefore, there are compelling reasons to investigate the energy consumption in buildings and its environmental impact. The current paper studies the effect of different retrofitting measures for reducing cooling load of buildings in hot climate. A common type of residential house with dimension of 12 × 12 × 3 m in Qatar was chosen as a case study. Five energy retrofitting measures of the building envelope have been considered in this study: (1) U-value of the external shell, (2) indoor set-temperature, (3) lighting efficacy, (4) the color of external shell, and (5) windows' quality. Hourly analysis program was used for calculating the cooling load of the case study. The anticipated costs associated with the implementation of the retrofitting measures were calculated based on the local current prices in Qatar. Simple payback period for each measure was assessed in the present study. The simulations show that the energy saving of 53% can be obtained at the working conditions of Qatar. The payback period of the examined measures is relatively short and varies between 0.5 and 4 years.